2021
DOI: 10.1503/jpn.200110
|View full text |Cite
|
Sign up to set email alerts
|

Threat-anticipatory psychophysiological response is enhanced in youth with anxiety disorders and correlates with prefrontal cortex neuroanatomy

Abstract: Background: Threat anticipation engages neural circuitry that has evolved to promote defensive behaviours; perturbations in this circuitry could generate excessive threat-anticipation response, a key characteristic of pathological anxiety. Research into such mechanisms in youth faces ethical and practical limitations. Here, we use thermal stimulation to elicit pain-anticipatory psychophysiological response and map its correlates to brain structure among youth with anxiety and healthy youth. Methods: Youth with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 61 publications
10
38
0
Order By: Relevance
“…Bayesian model comparison indicated that the best model included fixed effects of Group, Cue, and Trial, with random intercepts and random slopes for Cue and Trial (see Supplemental Results). Consistent with other studies of expectancy-based pain modulation (Atlas et al, 2010; Wiech et al, 2014; Reicherts et al, 2016; Fazeli and Büchel, 2018; Michalska et al, 2018; Abend et al, 2021), all models indicated that participants reported higher pain when medium heat was preceded by high pain cues than low pain cues (main effect of Cue: see Figure 2B and Table 2). Bayesian modeling indicated that this effect had a 100% probability of being positive (Median = 1.261, 89% CI [0.82, 1.338]), and can be considered practically significant (0% in ROPE).…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…Bayesian model comparison indicated that the best model included fixed effects of Group, Cue, and Trial, with random intercepts and random slopes for Cue and Trial (see Supplemental Results). Consistent with other studies of expectancy-based pain modulation (Atlas et al, 2010; Wiech et al, 2014; Reicherts et al, 2016; Fazeli and Büchel, 2018; Michalska et al, 2018; Abend et al, 2021), all models indicated that participants reported higher pain when medium heat was preceded by high pain cues than low pain cues (main effect of Cue: see Figure 2B and Table 2). Bayesian modeling indicated that this effect had a 100% probability of being positive (Median = 1.261, 89% CI [0.82, 1.338]), and can be considered practically significant (0% in ROPE).…”
Section: Resultssupporting
confidence: 88%
“…We measured whether cue-based expectancy effects on pain and brain responses to noxious heat update dynamically as contingencies change, and whether these relationships vary as a function of whether individuals learn through instruction or experience. All participants demonstrated robust cue-based expectancy effects on pain, consistent with previous work from our group and others (Colloca et al, 2008a; Atlas et al, 2010; Wiech et al, 2014; Fazeli and Büchel, 2018; Jepma et al, 2018; Michalska et al, 2018; Koban et al, 2019; Abend et al, 2021). Here, we provide new evidence that these predictive cue-based expectancy effects on pain update as contingencies change, whether reversals are accompanied by instructions or learned through experience.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations